Ottoman policy-making in an age of reforms: unearthing Ottoman archaeology in the 19th and early 20th centuries - Papatheodorou, A (2017)
This thesis discusses the Ottoman policies on archaeology in the aftermath of the initiation of the Tanzimat reforms (1839) and until the end of the Ottoman Empire (1923). It explores the activities of the central state, the autonomous Principality of Samos in the Aegean, and the Hellenic Literary Society at Constantinople. Primary and secondary sources in Ottoman Turkish, Katharevousa Greek, Modern Turkish and Modern Greek, English and French inform the analysis. The first chapter looks at the contexts within which an Ottoman interest in archaeology emerged. It discusses the rise of archaeology as a distinct area of scientific and scholarly research in the 19th and early 20th centuries, the encounters of the Ottomans with western archaeologies in that period, and those domestic intellectual dynamics that made them receptive to archaeology. The second chapter focuses on the Ottoman legislation on antiquities, and secondarily looks at related institutional developments. It discusses at length the emergence of an Ottoman voice on archaeology through the crystallisation of increasingly comprehensive and mature sets of rules and procedures on heritage management. By looking at the autonomous Principality of Samos, the third chapter shifts the attention to the western periphery of the empire, and explores how the Greek Orthodox, when outside the direct control of the central state, could develop their own understanding of, processes and structures regarding archaeology. The fourth chapter looks, for the first time in the literature, at the archaeological activities of the Hellenic Literary Society at Constantinople, and discusses the contribution of Ottoman society to the promotion of archaeological research and the protection of monuments. Overall, this thesis provides a critical analysis of the emergence of the concept and practice of archaeological heritage protection in the Ottoman Empire in the 19th and early 20th centuries.